Draft Genome Sequence of the Alicyclobacillus Acidocaldarius Strain lh1 Isolated from a Highly Acidic Solfatara Field - Blamey-Alegria, J (American Society for Microbiology, 2025)
The Alicyclobacillaceae are known for their ability to produce thermostable industrial catalysts, including endonucleases and hydrolases. Here, we report the draft genome sequence of the Alicyclobacillus acidocaldarius strain LH1, isolated from a highly acidic Andean solfatara in the Chilean Andes. © © 2025 Fuentes-Tobar et al.